THE WINE SECTOR SYSTEMS AND FINANCING IN EU VS ROMÂNIA SECTOR - Neacşu (Bleajă), Oniţa (Economics of Agriculture, 2012)
The main actors involved in wine-producers, national and European associations, national governments, European Parliament and European Commission had concerns over he time to find some measures for increasing the competitiveness of European wine. There were however a number of constraints in determining the measures of support for viticulture and wine in view of some international treaties that the EU has concluded in the WTO and other treaties on economic and agricultural subsidies, and the interests of individual Member States and optics, some wine-producing countries with different specific interests and others seeking financing as low as agriculture.